Perspektif Psikologi dan Sosiologi dalam Implementasi Pendidikan Islam - Jawaz, Yazid Abdul Qadir; Ningsih, Tutuk (At-Tadris: Journal of Islamic Education, 2024)
This study discusses the importance of sociological and psychological approaches in Islamic education to address the misunderstandings that frequently occur in interpreting religious messages among Muslims. Islamic education aims to shape individuals with good character, both outwardly and inwardly, while fostering a strong sense of brotherhood amidst modern challenges. This research employs a library research method using descriptive and content analysis approaches, collecting data from books, journal articles, and relevant digital sources. The findings reveal that the sociological approach plays a significant role in understanding the dynamics of faith that are internalized, comprehended, and practiced, as well as in highlighting sociology’s essence as a discipline that examines contemporary social phenomena. In conclusion, integrating the sociological approach into Islamic education is a strategic step toward creating a more harmonious society and achieving a holistic understanding of religion.